2017
DOI: 10.1177/1178223417731297
|View full text |Cite
|
Sign up to set email alerts
|

High Tangent Radiation Therapy With Field-in-Field Technique for Breast Cancer

Abstract: Purpose:We evaluated whether the field-in-field (FIF) technique improves the homogeneity of the target in high tangent radiation therapy (HTRT).Materials and Methods:This study included 30 patients. In total, 3 HTRT plans were created: 1 with conventional opposed fields (Conv-p), 1 with the FIF technique (FIF-p), and 1 with FIF technique using lung-blocked subfields (FIF-LB-p).Results:The maximum dose of the breast and planning target volume (PTV) was significantly lower for FIF-p and FIF-LB-p than Conv-p. Hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Adequate target coverage is associated with tumour control which leads to improve biochemical relapse-free survival, cancer progression-free survival and cancer-specific survival. Several studies [8][9][10][11][12][13][14][15][16]20,22,23,26,27,30 have reported similar PTV_eval coverage for breast cancer patients. Tanaka et al 16 investigated the FIF technique with lung blocks for breast radiotherapy and reported V 95% and V 100% of 93•2 and 62•7% for patients treated with the FB technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate target coverage is associated with tumour control which leads to improve biochemical relapse-free survival, cancer progression-free survival and cancer-specific survival. Several studies [8][9][10][11][12][13][14][15][16]20,22,23,26,27,30 have reported similar PTV_eval coverage for breast cancer patients. Tanaka et al 16 investigated the FIF technique with lung blocks for breast radiotherapy and reported V 95% and V 100% of 93•2 and 62•7% for patients treated with the FB technique.…”
Section: Resultsmentioning
confidence: 99%
“…When treating the intact breast or chest-wall for low-risk early stage patients, a pair of opposed tangential fields are usually employed. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However for high-risk patients with node positive disease or are at greater risk of nodal metastasis, radiation therapy will involve treatment of the intact breast or chestwall as well as the regional lymph nodes. This is achieved using two tangential fields to treat the intact breast or chest-wall and an anterior and sometimes opposed posterior fields to treat the regional lymph nodes in the upper axillary and supraclavicular regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the degree of incidental lymph node irradiation varied between the patients from 12.1 ± 19.2% of the prescribed dose (patient III) to 64.8 ± 17.8% of the prescribed dose (patient II). Differently from our study, most previous studies estimated the dose distribution in the lymph node areas as defined by RTOG or ESTRO guidelines [ 5 , 6 , 9 , 11 , 24 , 25 ]. However, these guidelines define a treatment volume and do not necessary reflect the whole axillary lymph node drainage system and both primary lymph node metastases and lymph node recurrences occur outside the ESTRO and RTOG margins [ 16 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic wedge filters and/or the field in field technique were used to obtain a homogeneous dose distribution. 6 , 7 In 3DCRT, 42.4 Gy in 16 fractions of 2.65 Gy was prescribed to the isocenter. A VMAT plan used dual partial arcs of 40° to 50° with a collimator angle of 30° and treatment couch angle of 0°, rotating in opposite directions.…”
Section: Methodsmentioning
confidence: 99%